The Long Claws of Fate - Bialonwu, Uche (Longman Nigeria Plc, 1988)
The Long Claws of Fate deals with the entangled fates of Titi Anukpo a widowed mother of six, and her son-in-law, Dr Akin Balogun. It explores the popularly held belief that an ill-fated life is unalterable, in escapable$1! =s
Keywords: Fiction